Answer:
Explanation:
The quadratic formula for a equation of form
ax²+bx + c = 0 is
![x= (-b +- √(b^2-4ac) )/(2a)](https://img.qammunity.org/2022/formulas/mathematics/college/usigx5bkg77qell5udlkamjxy856s15vce.png)
For the first equation,
x²+3x-4=0,
we can match that up with the form
ax²+bx + c = 0
to get that
ax² = x²
divide both sides by x²
a=1
3x = bx
divide both sides by x
3 = b
-4 = c
. We can match this up because no constant multiplied by x could equal x² and no constant multiplied by another constant could equal x, so corresponding terms must match up.
Plugging our values into the equation, we get
![x= (-3 +- √(3^2-4(1)(-4)) )/(2(1)) \\= (-3+-√(25) )/(2) \\ = (-3+-5)/(2) \\= -8/2 or 2/2\\= -4 or 1](https://img.qammunity.org/2022/formulas/mathematics/college/7zp34q344gocjjj3fmipt329ixy3zd01my.png)
as our possible solutions
Plugging our values back into the equation, x²+3x-4=0, we see that both f(-4) and f(1) are equal to 0. Therefore, this has 2 real solutions.
Next, we have
x²+3x+4=0
Matching coefficients up, we can see that a = 1, b=3, and c=4. The quadratic equation is thus
![x= (-3 +- √(3^2-4(1)(4)) )/(2(1))\\= (-3 +- √(9-16) )/(2)\\= (-3 +- √(-7) )/(2)\\](https://img.qammunity.org/2022/formulas/mathematics/college/qk3d95se1j0iqupywsugpzb9ljwx0e8yl2.png)
Because √-7 is not a real number, this has no real solutions. However,
(-3 + √-7)/2 and (-3 - √-7)/2 are both possible complex solutions, so this has two complex solutions
Finally, for
4x² + 1= 4x,
we can start by subtracting 4x from both sides to maintain the desired form, resulting in
4x²-4x+1=0
Then, a=4, b=-4, and c=1, making our equation
![x=(-(-4) +- √((-4)^2-4(4)(1)) )/(2(4)) \\= (4+-√(16-16) )/(8) \\= (4+-0)/(8) \\= 1/2](https://img.qammunity.org/2022/formulas/mathematics/college/ygv1v2ckdcvdmp82enbxlvmcb74md0oy9j.png)
Plugging 1/2 into 4x²+1=4x, this works as the only solution. This equation has one real solution